Role of Biodiversity in achieving nutritional food security - Kaur, Vikender; Kumar, Jyoti; Wankhede, D P; Srivastava, Vartika (Indian Farming, 2018)
The relationship between biodiversity and nutrition that seems to be evident from this article, suggests that there is need to pay close attention to the potential of integrated approaches. Managing landscapes on a multi-functional basis that combines food production, biodiversity conservation and the maintenance of ecosystem services should be at the forefront of efforts to achieve nutritional food security.